Recovery of rare earth elements from low-grade coal fly ash using a recyclable protein biosorbent - Hussain, Zohaib; Dwivedi, Divya; Kwon, Inchan (Frontiers in Bioengineering and Biotechnology, 2024)
Rare-earth elements (REEs), including the lanthanide series, are crucial components essential for clean energy transitions and originate from geographically limited regions. Exploiting new and diverse supply sources is vital to facilitate a clean energy future. Hence, we have explored the recovery of REEs from coal fly ash, a complex, low-grade industrial feedstock that is currently underutilized (leachate concentrations of REEs in FA is <0.003 mol %). Herein we demonstrated the thermo-responsive genetically encoded REE-selective elastin-like polypeptides (RELP) as a recyclable bioengineered protein adsorbent for the selective retrieval of REEs from coal fly ash over multiple cycles. The results showed that RELP could be efficiently separated using temperature cycling and reused with high stability, as it retained ∼95% of the initial REE binding capacity even after four cycles. Moreover, RELP selectively recovered high-purity REE from the simulated solution containing one representative REE in the range of 0.0001 to 0.005 mol%, resulting in up to 100,000-fold increase in REE purity. This study offers a sustainable approach to diversify REE supplies by recovering REEs from low-grade REEs in industrial wastes and provides a scientific basis for extraction of high-purity REEs for industrial purposes.